2022
DOI: 10.1021/acsabm.2c00439
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Photodynamic Antibacterial Activity of NH2-MIL-101(Fe)@MoS2/ZnO Ternary Composites

Abstract: Bacterial infections are a serious threat to human health, and the development of effective antibacterial agents represents a critical solution. In this study, NH2-MIL-101­(Fe)@MoS2/ZnO ternary nanocomposites are successfully prepared by a facile wet-chemistry procedure, where MoS2 nanosheets are grown onto the MIL-101 scaffold forming a flower-like morphology with ZnO nanoparticles deposited onto the surface. The ternary composites exhibit a remarkable sterilization performance under visible light irradiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 51 publications
(83 reference statements)
1
3
0
Order By: Relevance
“…1a. It could be found that NH 2 -MIL-101 exhibited characteristic peaks at 8.9°, 10.3°, 16.4°, 20.2°, and 24.5°, which were consistent with the data reported in the literature, 29,34,35 indicating that the pure phase NH 2 -MIL-101 material was successfully prepared. Furthermore, the characteristic peaks of TiO 2 at 25.34° and 48.04° could also be observed.…”
Section: Resultssupporting
confidence: 90%
“…1a. It could be found that NH 2 -MIL-101 exhibited characteristic peaks at 8.9°, 10.3°, 16.4°, 20.2°, and 24.5°, which were consistent with the data reported in the literature, 29,34,35 indicating that the pure phase NH 2 -MIL-101 material was successfully prepared. Furthermore, the characteristic peaks of TiO 2 at 25.34° and 48.04° could also be observed.…”
Section: Resultssupporting
confidence: 90%
“…116 The Z-scheme heterojunction, on the other hand, offers a more efficient charge separation and transfer mechanism, but requires a more complex and precise design. 115 In our previous research, a ternary composite photocatalyst material NH 2 -MIL-101(Fe)@MoS 2 /ZnO has been designed with both a step-scheme heterojunction and P-N junction, which exhibits high-efficiency photodynamic antibacterial activity, 144 as illustrated in Fig. 9.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…4, which exhibited significant bactericidal performance against both Gram-negative and Gram-positive bacteria under visible light irradiation, with a killing rate of 98.6% for E. coli and 90% for S. aureus after 30 minutes of visible light irradiation. 42 The antibacterial properties of Fe-MOFs make them promising candidates for antibacterial therapy. With further research into the properties and applications of these materials, it is expected that Fe-MOFs will have more opportunities for use in antibacterial therapy.…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%
“…4, which exhibited significant bactericidal performance against both Gram-negative and Gram-positive bacteria under visible light irradiation, with a killing rate of 98.6% for E. coli and 90% for S. aureus after 30 minutes of visible light irradiation. 42…”
Section: Application Of Mil-100(fe) and Mil-101(fe) In Antibacterial ...mentioning
confidence: 99%